2010
DOI: 10.1073/pnas.1006542107
|View full text |Cite
|
Sign up to set email alerts
|

Programmed necrosis induced by asbestos in human mesothelial cells causes high-mobility group box 1 protein release and resultant inflammation

Abstract: Asbestos carcinogenesis has been linked to the release of cytokines and mutagenic reactive oxygen species (ROS) from inflammatory cells. Asbestos is cytotoxic to human mesothelial cells (HM), which appears counterintuitive for a carcinogen. We show that asbestos-induced HM cell death is a regulated form of necrosis that links to carcinogenesis. Asbestos-exposed HM activate poly(ADP-ribose) polymerase, secrete H 2 O 2 , deplete ATP, and translocate high-mobility group box 1 protein (HMGB1) from the nucleus to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
255
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 236 publications
(268 citation statements)
references
References 38 publications
(64 reference statements)
10
255
1
2
Order By: Relevance
“…Further studies in human mesothelial cells confirmed that asbestos exposure caused priming of NLRP3 (increased mRNA levels) as well as its activation (Shukla et al, 2003;2011). In support of our work, Yang et al (2010) showed the release of high mobility group box-1 protein (HMGB-1) from asbestosexposed mesothelial cells (Yang et al, 2010). The release of HMGB-1 may possibly occur via inflammasome-induced pyroptosis, an inflammation-mediated cell death process dependent on inflammsome activation of caspase-1.…”
Section: Introductionsupporting
confidence: 66%
“…Further studies in human mesothelial cells confirmed that asbestos exposure caused priming of NLRP3 (increased mRNA levels) as well as its activation (Shukla et al, 2003;2011). In support of our work, Yang et al (2010) showed the release of high mobility group box-1 protein (HMGB-1) from asbestosexposed mesothelial cells (Yang et al, 2010). The release of HMGB-1 may possibly occur via inflammasome-induced pyroptosis, an inflammation-mediated cell death process dependent on inflammsome activation of caspase-1.…”
Section: Introductionsupporting
confidence: 66%
“…HMGB1 contributes to the development of malignant mesotheliomain response to the exposure of mesothelial cells to asbestos. 31,32 Conversely viable mesothelioma cells actively secrete HMGB1: interference with HMGB1 or with the RAGE receptors limits the growth of human xenografts in immunodeficient mice, 33 supporting the contention that the molecule can play cancer-supporting actions in the extracellular environment. 34 Cell death occurring after chemotherapy with cytotoxic agents substantially increases the extent of HMGB1 released from MC-38 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The doses of the compounds and recombinants were selected based on previous reports. 20,49 Eyes that sustained marked surgical trauma (for example, retinal or subretinal hemorrhage, bacterial infection) were excluded from further analyses.…”
Section: Discussionmentioning
confidence: 99%